2010
DOI: 10.1056/nejmoa1003795
|View full text |Cite
|
Sign up to set email alerts
|

Severe Hypoglycemia and Risks of Vascular Events and Death

Abstract: Severe hypoglycemia was strongly associated with increased risks of a range of adverse clinical outcomes. It is possible that severe hypoglycemia contributes to adverse outcomes, but these analyses indicate that hypoglycemia is just as likely to be a marker of vulnerability to such events. (Funded by Servier and the National Health and Medical Research Council of Australia; ClinicalTrials.gov number, NCT00145925.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

44
1,013
7
46

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,327 publications
(1,110 citation statements)
references
References 29 publications
44
1,013
7
46
Order By: Relevance
“…ACCORD did not evaluate a direct effect of hypoglycaemia on risk of cardiovascular death or determine a definite reason for increased cardiovascular death among patients treated intensively. By contrast, the ADVANCE study found higher risk in patients who had an episode of severe hypoglycaemia for vascular events, cardiovascular death and death from any cause – and speculated such hypoglycaemia episodes could be only markers for susceptibility; any causative contribution of hypoglycaemia to risk of cardiovascular events remains uncertain 1, 13. More recent results from the SAVOR‐TIMI 53 study in patients with T2DM and renal impairment have shown an increase in hypoglycaemia and major cardiovascular events in patients with moderate but not severe renal impairment, potentially attributable to higher rates of concomitant medication use in the moderately impaired group 14…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ACCORD did not evaluate a direct effect of hypoglycaemia on risk of cardiovascular death or determine a definite reason for increased cardiovascular death among patients treated intensively. By contrast, the ADVANCE study found higher risk in patients who had an episode of severe hypoglycaemia for vascular events, cardiovascular death and death from any cause – and speculated such hypoglycaemia episodes could be only markers for susceptibility; any causative contribution of hypoglycaemia to risk of cardiovascular events remains uncertain 1, 13. More recent results from the SAVOR‐TIMI 53 study in patients with T2DM and renal impairment have shown an increase in hypoglycaemia and major cardiovascular events in patients with moderate but not severe renal impairment, potentially attributable to higher rates of concomitant medication use in the moderately impaired group 14…”
Section: Discussionmentioning
confidence: 99%
“…The ADVANCE investigators highlighted the potential contribution of confounding to their reported association13; however, a recent meta‐analysis which included data on six large observational studies involving >900 000 patients used a statistical approach – bias analysis – to show that confounding as a result of comorbid severe illness was unlikely to explain the whole association 5. The authors concluded that there was, in fact, a strong likelihood of a direct relationship between hypoglycaemic episodes and subsequent cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, hypoglycaemia may be life-threatening [4,5]. While hyperglycaemia is the characteristic feature of diabetes [3], patients with diabetes may also be susceptible to hypoglycaemia due to the nature of the disease [4] and treatment [6].…”
Section: Introductionmentioning
confidence: 99%
“…We screened 1273 citations and included 17 studies with a total of 1498358 participants in the meta-analysis (Bonds et al, 2010, Chiba et al, 2015, Duckworth et al, 2011, Hsu et al, 2013, Origin Trial Investigators et al, 2013, Johnston et al, 2012, Johnston et al, 2011, Khunti et al, 2015, Majumdar et al, 2013, McCoy et al, 2012, Rajpathak et al, 2015, Rathmann et al, 2013, Signorovitch et al, 2013, Zhao et al, 2012, Zoungas et al, 2010. The flow chart of the study selection in shown in the supplementary eFigure.…”
Section: Resultsmentioning
confidence: 99%